Immature glandular features in squamous cell carcinoma of the uterine cervix as an independent indicator of resistance to radiotherapy. Issue 3 (1st April 2002) - Okada, S; Tsuda, H; Ohmi, K; Kasamatsu, T; Yamada, T; Tsunematsu, R; Sumi, M; Tokuuye, K; Yoshikawa, H; Hirohashi, S
Abstract : Abstract: Okada S, Tsuda H, Ohmi K, Kasamatsu T, Yamada T, Tsunematsu R, Sumi M, Tokuuye K, Yoshikawa H, Hirohashi S. Immature glandular features in squamous cell carcinoma of the uterine cervix as an independent indicator of resistance to radiotherapy. The aim of this study was to evaluate the significance of "immature glandular features" in cervical squamous cell carcinoma (SCC) as an indicator of tumor radioresistance. Pretreatment biopsied tissue specimens of cervical SCC from 100 patients who were uniformly treated with radiotherapy alone were classified into clinically radioresistant (cR) and radiosensitive (cS) groups. Seven histologic parameters comprising glassy cells, signet ring cells, squamous differentiation, recognizable gland, nuclear atypia, stromal response, and mitotic counts were examined. Glassy cells and signet ring cells were regarded as "immature glandular features". The correlation of these seven parameters with tumor response to radiotherapy and patient prognosis was analyzed by univariate and multivariate analyses. As objective indicators of glandular differentiation, alcian-blue staining and immunostaining of cytokeratins 7 and 20 were also performed. It was revealed that immature glandular features, absence of squamous differentiation, and low nuclear atypia were significant indicators of radioresistance of the tumor and of poorer patient prognosis. Combining those histological parameters, the present SCC cases were classified into 26 pathologically radioresistant (pR) and 74 radiosensitive (pS) groups. In the pR group, 54% (14 of 26) were clinically radioresistant, whereas 20% (15 of 74) of the pS group were clinically radioresistant ( P = 0.002). The overall prognosis of the pR group was much poorer than that of the pS group ( P < 0.0001). This correlation also held true in cases of identical stage and age. We could not show objectively glandular differentiation of "immature glandular features". Nonetheless, the identification of "immature glandular features" was effective in predicting the radiotherapy resistance of cervical SCC and poorer patient prognosis.